Case–control study to identify risk factors for SARS‐CoV‐2 infection among university students in the northeastern USA. Issue 5 (29th June 2022) - Cummings, Kevin J.; Clarkberg, Marin; Busche, Jefferson; Travis, Alexander J.; Meredith, Genevive R.; Weisfuse, Isaac; Cazer, Casey L.; Koretzky, Gary A.; Warnick, Lorin D.
Abstract: Curbing the coronavirus disease 2019 (COVID‐19) pandemic requires a thorough understanding of risk factors for transmission of SARS‐CoV‐2, the etiologic agent. Institutions of higher education present unique challenges for controlling disease spread because of features inherent to these settings. Our objective was to determine risk factors for SARS‐CoV‐2 infection among a university student population in the northeastern USA during the spring and fall 2021 semesters, using the case–control study design. Cases were defined as students with a newly diagnosed SARS‐CoV‐2 infection detected either through the robust PCR‐based surveillance testing program on campus or through healthcare testing if symptoms compatible with COVID‐19 were present. Controls were defined as students with negative SARS‐CoV‐2 status, based on consistently negative PCR results at the time of selection. A comprehensive questionnaire was administered to each student enrolled in the study, covering a broad range of campus life activities. A total of 446 cases and 1, 185 controls were included in this study. Multivariable logistic regression analysis showed that recent party attendance (adjusted OR = 2.3, p < .0001), recently visiting a bar (aOR = 1.6, p = .007), living in a campus residence hall (aOR = 1.6, p = .001), fraternity/sorority membership (aOR = 1.8, p = .002), and recent travel (aOR = 1.3, p = .04) were associated with being a COVID‐19 case. Having an on‐campus job was negatively associated with being a COVID‐19 case (aOR = 0.6, p = .0003). Among cases, the most commonly reported symptoms were cough (43.9%), fatigue (38.1%) and sore throat (30.3%). These findings can be used to inform the development of COVID‐19 mitigation strategies and public health outreach efforts in university settings, thus reducing SARS‐CoV‐2 transmission among students and helping to preserve the vital education and research missions of these institutions.